2014
DOI: 10.1063/1.4863319
|View full text |Cite
|
Sign up to set email alerts
|

Hopping process of bound excitons under an energy gradient

Abstract: We report on the mechanism of hopping for bound excitons under an energy gradient. By means of a Monte-Carlo simulation, we show that this mechanism explains the movement of bound excitons observed experimentally. We show that the speed of the excitons decreases quickly with temperature. Thanks to an effective medium approximation, we deduce an analytical model to estimate the average speed at T ¼ 0 K. Finally, we compare our simulations results to the speed observed in bent ZnO wires and find a good agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…As shown in Figs. 3(c) and 3(d), the good agreement between our experimental results and the fits (blue lines) allows us to clearly identify the effective radius of dislocation 14,21 Note that the CL intensity at initial delay is defined as I CL ðr 0 ; t ¼ 0Þ / n 0 N =s r . Considering that no diffusion happens at this moment, the decrease of I CL ðr 0 ; t ¼ 0Þ near the dislocation can be due to either the increase of s r or the reduction of n 0 .…”
Section: -mentioning
confidence: 52%
“…As shown in Figs. 3(c) and 3(d), the good agreement between our experimental results and the fits (blue lines) allows us to clearly identify the effective radius of dislocation 14,21 Note that the CL intensity at initial delay is defined as I CL ðr 0 ; t ¼ 0Þ / n 0 N =s r . Considering that no diffusion happens at this moment, the decrease of I CL ðr 0 ; t ¼ 0Þ near the dislocation can be due to either the increase of s r or the reduction of n 0 .…”
Section: -mentioning
confidence: 52%
“…However, when raising the temperature, the backward motion of excitons activated by thermal energy affects dramatically the average speed of excitons along the strain gradient. The average speed of D X A s predicted to decrease by almost a factor of 10, when raising the temperature from 0 K to 30 K. 8 Therefore, this model predicts two main features for the hopping process of excitons: (i) the independence of the exciton speed from the energy gradient value at low temperature and (ii) a strong thermal quenching of the exciton speed.…”
mentioning
confidence: 99%
“…Since the exciton hopping rate is independent of the energy gradient, 8 instead of the drift-diffusion model applied in Ref. 7, Equation (2) has been solved by finite difference methods to estimate the exciton speed from our measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, several studies reported the effects of different deformation potentials on the NBE band shift of ZnO nanowires and microwires2930313233. Recently, it was found that the neutral-donor-bound excitons of bent ZnO microwires drifted towards and emitted photons at the tensile side through a hopping process at liquid helium temperature343536. In addition, it was reported that a transverse piezoelectric field could produce separated electrons and holes that drifted to the tensile and compressive sides, respectively, which led to a net redshift of free-exciton PL emission in the bent ZnO nanowire37.…”
mentioning
confidence: 99%